PENGARUH PENAMBAHAN TEPUNG BAWANG PUTIH PADA RANSUM TERHADAP PRODUKTIVITAS AYAM PETELUR FASE LAYER UMUR 20 MINGGU (The Effect of Garlic Powder Supplementation in Feed on the Productivity of 20-Week-Old Laying Hens in the Layer Phase) - Hermawan, Rio Dicky; Afiyah, Dyah Nurul; Rohmad, Rohmad (Universitas Nusa Cendana, 2025)
The purpose of this study was to determine the effect of adding garlic powder to feed on the productivity of 20-week-old laying hens. This study was conducted in Wonorejo Village, Wates District, Kediri Regency, from January 26 to March 9, 2025. The research method used a completely randomized design (CRD) consisting of 4 treatments with 5 replicates, and each replicate consisted of 2 laying hens aged 20 weeks. The treatments were P0 with 0% garlic powder addition, P1 with 0.5% garlic powder addition, P2 with 1% garlic powder addition, and P3 with 1.5% garlic powder addition. The variables observed were feed intake, number of eggs, egg weight, and feed conversion. The results of this study indicate that the addition of garlic powder to the feed of 20-week-old laying hens has a significant effect on feed consumption, egg production, and feed conversion (P<0.05). Treatments P1 and P2 produced average feed consumption and egg weight that were not significantly different but higher than P0 and P3. The highest number of eggs was obtained in treatment P1, which showed a higher average than P0, P2, and P3. In addition, treatment P1 also showed the lowest feed conversion rate, indicating better feed utilization efficiency, because the lower the feed conversion rate, the higher the feed efficiency. The conclusion of this study shows that P1 produced the best production performance, as indicated by higher average feed consumption, number of eggs, and egg weight compared to P0, P2, and P3. In addition, the feed conversion ratio in P1 was also the most efficient because it showed a lower average than treatments P0, P2, and P3